Toxicological and behavioral analyses indicates the safety of a biofertilizer in the non-target D. melanogaster. - Rieder, G.S.; Zamberlan, D.C.; Silva, L.F.O.; Borin, B.C.; Schuch, A.P.; da Rocha, J.B.T. (Science of the Total Environment, 2023)
The demand for food to feed the growing world population has been promoting the indiscriminate use of chemical fertilizers, which can be detrimental to the environment. In order to maintain high crop productivity without damaging the ecosystem, biofertilizers have emerged as alternative to reduce the use of chemical fertilizers. So, environmentally safer biofertilizer can replace the exploitation of more toxic chemical fertilizer. Here, the fly Drosophila melanogaster was used to study the potential toxicity of the biofertilizer Beifort®. Flies were exposed to high concentrations of Beifort® in the diet (1.8 mL/L, 9.0 mL/L and 18 mL/L), and morphological and behavioral endpoints of toxicity were analyzed (development from egg to adult age, flies longevity, climbing performance, memory and learning of an associative learning, larvae digestive tract damage and plasmid DNA break). Beifort® did not modify flies development, survival, digestive track cell damage, locomotor activity or memory. Beifort® did not induce DNA breakage in vitro and had no toxicity to the non-target D. melanogaster after in vivo exposure. Thus, in addition of promoting the sustainable use of agricultural wastes, the exploitation of Beifort® can contribute to decrease the use of chemical fertilizers.